Resilience and Negotiation: Ancestral Belief Adherents Facing Discrimination in Indonesia - Haryono, Benjamin; Tjipto, Susana (Jurnal Psikologi, 2024)
Adherents of indigenous beliefs have long been a part of Indonesia's diverse cultural landscape and have historically faced significant discrimination, making it crucial to understand how resilience in these individuals affects their empowerment and well-being. This study aims to understand the resilience of followers adherents of indigenous belief systems in dealing with the phenomenon of fluctuating recognition of their religious traditions in Indonesia. Informants in this study were chosen based on the criteria of the research objective: adherents of indigenous beliefs aged over 45 years who had experienced the phenomenon of fluctuating recognition of indigenous beliefs. Three informants were involved (two males and one female, aged 49 to 68 years old). Data were collected through semi-structured, in-depth individual interviews, and a descriptive phenomenological approach was used for data analysis. The study identified one main theme: negotiation used to confront power asymmetries. Two forms of negotiation were found: self-negotiation and negotiation with others. Self-negotiation strategies include emotional regulation and adaptive actions towards life events. Negotiation with others involves effective communication and efforts to obtain rights and recognition both legally and socially. Through negotiation, adherents of indigenous beliefs can be resilient, even when this method does not change the existing power asymmetries. The implications of this study highlight the necessity for a collective movement to advocate for the recognition of both legal and social rights for all faiths.